Intramedullary screw fixation with bone autografting to treat proximal fifth metatarsal metaphyseal-diaphyseal fracture in athletes: a case series - Tsukada Sachiyuki; Ikeda Hiroo; Seki Yoshie; Shimaya Masayuki; Hoshino Akiho; Niga Sadao (BMC, 2012)
Abstract Background Delayed unions or refractures are not rare following surgical treatment for proximal fifth metatarsal metaphyseal-diaphyseal fractures. Intramedullary screw fixation with bone autografting has the potential to resolve the issue. The purpose of this study was to evaluate the result of the procedure. Methods The authors retrospectively reviewed 15 athletes who underwent surgical treatment for proximal fifth metatarsal metaphyseal-diaphyseal fracture. Surgery involved intramedullary cannulated cancellous screw fixation after curettage of the fracture site, followed by bone autografting. Postoperatively, patients remain non weight-bearing in a splint or cast for two weeks and without immobilization for an additional two weeks. Full weight-bearing was allowed six weeks postoperatively. Running was permitted after radiographic bone union, and return-to-play was approved after gradually increasing the intensity. Results All patients returned to their previous level of athletic competition. Mean times to bone union, initiation of running, and return-to-play were 8.4, 8.8, and 12.1 weeks, respectively. Although no delayed unions or refractures was observed, distal diaphyseal stress fractures at the distal tip of the screw occurred in two patients and a thermal necrosis of skin occurred in one patient. Conclusions There were no delayed unions or refractures among patients after carrying out a procedure in which bone grafts were routinely performed, combined with adequate periods of immobilization and non weight-bearing. These findings suggest that this procedure may be useful option for athletes to assuring return to competition level.